Microstructure, Tribological Properties and Corrosion Behaviour of Additively Manufactured 17-4PH Stainless Steel: Effects of Scanning Pattern, Build Orientation, and Single vs. Double scan. (December 2020) - Lashgari, H.R.; Xue, Y.; Onggowarsito, C.; Kong, C.; Li, S.
Highlights: Weld pool geometry in the hexagon scanning pattern was wider than the concentric scanning pattern. Remelting reduced porosities and volume fraction of retained austenite leading to enhanced wear resistance. Hexagon scanning pattern led to better wear resistance than the concentric pattern owing to less porosities Oxidative/abrasive wear was found be the main wear mechanism, Porosities caused instability of the protective oxide and pitting corrosion Abstract: The aim of the present study is to investigate the effect of different process parameters, i.e. scanning pattern (hexagonal vs. concentric), build orientation (vertical vs. horizontal), and single scan vs. double scan on the microstructure, wear resistance and corrosion properties of additively manufactured 17-4PH stainless steel by means of advanced material characterization techniques such as X-ray diffraction (XRD), electron back scatter diffraction (EBSD), and scanning electron microscopy (SEM). The volume fraction of retained austenite varied from 0.7% to 4.4% based upon the orientation and scanning strategy. In both scanning patterns, the maximum variation of nanohardness (along the build-axis and perpendicular to the build axis) was observed in the vertically printed samples using the single scan whereas the double-scan strategy (remelting) decreased the variation in both scanning patterns via lowering the temperature gradient and cooling rate. Remelting enhanced the wear resistance (by almost ≈50%) by decreasing the volume fraction of pores and balling defects up to ≈60-70% in the hexagon and concentric scanning pattern. The build orientation (vertical vs. horizontal) had more influence on the wear resistance in the concentric scanning pattern than that of hexagon pattern. Oxidative/abrasive wear was found to be the dominant wear mechanism during the reciprocating action in both scanning patterns; however, the oxide film was more prone to fracture in the samples fabricated by the concentric pattern due to the presence of more micropores in the matrix especially in the areas where laser direction changed. In the phosphate-buffered saline (PBS) solution, the corrosion rate of the samples manufactured using the hexagonal scanning pattern was generally less than those manufactured using the concentric pattern owing to the lower porosity. The lower breakdown potential in the concentric scanning pattern indicates that the protective passive layer is broken down easily making it susceptible to pitting corrosion due to the presence of porosities between the laser tracks. The Inductively Coupled Plasma (ICP) analysis revealed that the sample fabricated using single scan with hexagon scanning pattern and orientated vertically released the least amount of ions in the PBS solution, showing the significance for understanding the effect of additive manufacturing parameters on functional materials.